Efektifitas Absensi Online dalam Disiplin Kerja di Kantor Imigrasi Khusus TPI Surabaya Saat Pandemi Covid-19 - Muhammad Arifin; Agus Widiyarta (Sawala : Jurnal Administrasi Negara, 2021)
This study aims to find out the effectiveness of online attendance in the discipline of work in immigration office class I Special TPI Surabaya during the covid-19 pandemic. This study uses a qualitative approach. Data collection techniques using interview techniques are associated with the theory of program effectiveness indicators (Budiani, 2007). The results showed that the application of online attendance at immigration office immigration class I Special TPI Surabaya during the covid-19 pandemic has been effective in controlling attendance discipline. Based on the accuracy of the program shows the application of online attendance in the immigration office goes well in accordance with the target that is to all employees of the immigration office and existing regulations. From the indicators of program socialization to office employees run effectively because it has been done evenly to all employees through online. The purpose of the online attendance program at the immigration office in accordance with the plan to avoid the spread of corona virus because since March has circulated a lockdown circular. Based on the monitoring of the online attendance program at the immigration office has been implemented well by the staff and the public. From the results of the recap of employee attendance data will be evaluated in order to be the calculation of hours of entry and return to work seen from the entry and lateity of employees doing attendance which will then be done discounted allowances.